Knowledge and practices on contraception among married female school teachers in Udunuwara MOH area and the use by them of available family planning services - Fernando, K.J. N (My University, 1999)
Contraceptive prevalence rate was only 52 percent among teachers, which was lower than the national prevalence and non user rate was high among the teachers above 45 years of age. Sinhalese teachers recorded a significantly higher knowledge on modern permanent methods than Muslim teachers did. Either the subjects they teach or the academic qualifications they possess did not show any significant association with knowledge. The teachers' knowledge on natural and traditional methods was better than the knowledge they had on both modern temporary and modern permanent methods